FAKTOR-FAKTOR YANG MEMPENGARUHI ORGANIZATION CITIZENSHIP BEHAVIOUR (OCB) DI PT. CHING LUH INDONESIA - Atik Atikah (Value : Jurnal Manajemen dan Akuntansi, 2020)
The purpose of this study was to determine the effect of Organizational Commitment, Job Satisfaction, and Organizational Culture on Organization Citizenship Behavior (OCB) either partially or simultaneously at PT. Ching Luh Indonesia. This study uses an associative method with a quantitative approach. Sampling was 99 people. Data collection techniques and tools are literature study, observation and questionnaires or questionnaires. The data analysis technique used is descriptive analysis to determine the description of respondents' responses and data distribution, while inferential statistics are used for hypothesis testing. Data processing is assisted by Microsoft Excel and SPSS software version 23. If it is projected that the higher the value of Organizational Commitment (X1), Job Satisfaction (X2) and Organizational Culture (X3) at a certain value simultaneously, it will increase Organizational Citizenship Behavior (Y) at a certain value as well. Partially Job Satisfaction has a positive and significant effect on Organizational Citizenship Behavior (Y). While Organizational Commitment (X1) and Organizational Culture (X3) have no significant positive effect on Organizational Citizenship Behavior (Y). Keywords: Organizational Commitment, Job Satisfaction, Organizational Culture, Organizational Citizenship Behavior